2004
DOI: 10.1080/02786820490422880
|View full text |Cite
|
Sign up to set email alerts
|

Airborne Fine and Ultrafine Particles Near the World Trade Center Disaster Site

Abstract: Documentation of the airborne fine and ultrafine particles produced by the terrorist attack on the World Trade Center (WTC), particularly while fires were burning, was essential for evaluating the risk of adverse health effects in people who live and work in this area. We collected airborne particles for 3 months at a site about 400 m east of the former WTC.Ultrafine particles were collected by deposition onto small detector chips for morphometric analysis by atomic force microscopy. Some chips were coated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Two new types of iron nanofilm detectors (namely Fe-Ti-MS and Fe-MS) were developed, which were stable even after 3-month exposure to ambient air at a sampling site (Wang et al 2012); (3) development of sampling schedules based on the ambient particle number (PN) concentration. No acidic particles were detected in the previous study in New York (Cohen et al 2004b), suggesting that the method might either not be suitable for an airshed with low levels of air pollutants, or it should be improved. To ensure sufficient particles to be collected on the detectors for subsequent statistical analysis, and to avoid collected particles landing on one another resulting in underestimation of smaller particles and over-measurement of larger particles, the sampling duration was altered depending on the ambient PN concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Two new types of iron nanofilm detectors (namely Fe-Ti-MS and Fe-MS) were developed, which were stable even after 3-month exposure to ambient air at a sampling site (Wang et al 2012); (3) development of sampling schedules based on the ambient particle number (PN) concentration. No acidic particles were detected in the previous study in New York (Cohen et al 2004b), suggesting that the method might either not be suitable for an airshed with low levels of air pollutants, or it should be improved. To ensure sufficient particles to be collected on the detectors for subsequent statistical analysis, and to avoid collected particles landing on one another resulting in underestimation of smaller particles and over-measurement of larger particles, the sampling duration was altered depending on the ambient PN concentration.…”
Section: Introductionmentioning
confidence: 99%
“…The larger surface-to-volume ratios in the UP fraction probably encourage this condensation. Cohen et al (2004) measured PM 2.5 PAH as high as 1,500 ng/m 3 , reflecting the intensity of emissions from fires soon after the 9/11/2001 World Trade Center attack. Fine et al (2004) sought contributions from cooking and wood burning by using levoglucosan and cholesterol as organic markers for these sources.…”
Section: Up Compositionmentioning
confidence: 99%
“…Gasparini et al (2004) reported TDMA measurements from Houston to evaluate hygroscopic properties. MOUDI measurements were also taken by Cohen et al (2004) in New…”
Section: Monitoring Locationsmentioning
confidence: 99%
“…Only with this information can effective control measures be formulated and implemented. However, no reliable measurement techniques were available to obtain the number concentrations of AUFPs until 2012, as earlier methods can only identify the AUFPs in the atmosphere, but cannot quantify them (Wang et al, 2012;Cohen et al, 2004). Two methods were developed by our group in 2012 and 2014, respectively, to measure the AUFPs in the atmosphere with the nano-film detectors (i.e.…”
Section: Introductionmentioning
confidence: 99%